Kewajiban dan Pelatihan Perpajakan dalam Rangka Menumbuhkan Ketataatan Wajib Pajak Terhadap UMKM Kotamara Kecamatan Butupoaro Kota Baubau di Tengah Pandemik Covid-19 - Rudi Abdullah; Isan Tamsir; Yusril Yusril; Herlian Herlian; W.D. Zulfiyani; Hasliani Hasliani; Muhammad Rolis; Awi Fara; Mayang Mayang (Pelita: Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of this exercise of devotion is to give tax insight into the micro, small and medium enterprises (MSME) in the region of baubau, the coast of kotamara, kec. Batupoaro. the issue taken on the taxation of MSME. In this method of devoted activities that are, (a) a preparatory stage, which includes activity; early surveys, location determination and stabilization, and materials creation training. The results of this dedicated activity were highly beneficial to MSME, Baubau City, Kotamara Beach, Batupoaro Districts makes for knowledge and gives more insight on the taxation of MSME autism.